2010
DOI: 10.1515/jpm.2010.060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extremely low birth weight infants with varying doses and intervals of antenatal steroid exposure

Abstract: Beneficial impact of ANS on mortality and composite BPD/mortality is evident only after a complete course and persists even with its administration beyond a week from delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 16 publications
1
36
0
1
Order By: Relevance
“…It has previously been demonstrated that only a complete course of steroids confers survival benefit and reduction in IVH for infants born 23–26 weeks; a benefit that persists even if administration of steroids is more than 7 days from delivery 20. Our data, in line with existing literature, shows that only infants who received a full course of steroids more than 48 h prior to delivery obtained the benefits of steroids.…”
Section: Discussionsupporting
confidence: 89%
“…It has previously been demonstrated that only a complete course of steroids confers survival benefit and reduction in IVH for infants born 23–26 weeks; a benefit that persists even if administration of steroids is more than 7 days from delivery 20. Our data, in line with existing literature, shows that only infants who received a full course of steroids more than 48 h prior to delivery obtained the benefits of steroids.…”
Section: Discussionsupporting
confidence: 89%
“…Antenatal corticosteroids are known to reduce the occurrence of patent ductus arteriosus and IVH. [41][42][43][55][56][57][58][59] Systematic reviews and meta-analyses of the studies of prophylactic postnatal indomethacin have confirmed the significant reduction in severe IVH. In 14 trials including over 2,500 newborns, a 35% reduction in severe IVH was evident (RR 0.66 [95% CI, 0.53-0.82], P,.001).…”
Section: The First Weekmentioning
confidence: 91%
“…[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Some of these interventions pose little risk to the mother while others impose a significant burden.…”
Section: Obstetric Carementioning
confidence: 99%
See 1 more Smart Citation
“…Je nachdem, ob histologische oder klinische Chorioamnionitis als Kriterium herangezogen wurde, fanden sich signifikante Vorteile für verschiedene Endpunkte nach Gabe von Steroiden [20]. Dass ein kompletter Zyklus antenataler Steroide Vorteile hat gegenüber einem begonnen oder gar keinen Steroiden, legt nicht nur die klinische Erfahrung nahe, sondern ließ sich auch in einer monozentrischen, retrospektiven Untersuchung zeigen [21]. Dementsprechend lässt sich der Effekt auf die Reduktion pulmonaler Morbidität weiter senken, wenn im Abstand von 14 Tagen regelmäßig Steroide gegeben werden.…”
Section: Datenlageunclassified